Why Not Just Features? Reconsidering Infants’ Behavior in Individuation Tasks - Hildebrandt, Frauke; Lonnemann, Jan; Glauer, Ramiro (Frontiers in Psychology, 2020)
It counts as empirically proven that infants can individuate objects. Object individuation is assumed to be fundamental in the development of infants' ontology within the object-first account. It crucially relies on an object-file system, representing both spatiotemporal ("where") and categorical ("what") information about objects as solid, cohesive bodies moving continuously in space and time. However, infants’ performance in tasks requiring them to use featural information to detect individuation violations appears to be at odds with the object-first account. In such cases, infants do not appear to be able to develop correct expectations about the numerosity of objects. Recently, proponents of the object-first account proposed that these individuation failures result from integration errors between the object file system and an additional physical reasoning system (Stavans et al., 2019). We are going to argue that the predictions of the feature-based physical-reasoning system, as presented by Stavans et al., are sufficient for explaining infants’ behaviour. The striking predictive power of the physical-reasoning system calls into question the relevance of the object-file system and, thereby, challenges the assumption that infants can individuate objects early on.